SYLLABI PREPARATION AND UTILIZATION IN COLLEGE TEACHING - Odivilas, Hilarion A. (European Scientific Journal, ESJ, 2015)
A curriculum plan served as a blueprint to anticipate an expected outcome (Inocian, 2013) that necessitated a better planning. This study investigated the faculty profile, the adequacy of preparation and utilization of syllabi and their instructional problems in the undergraduate studies; adopted the descriptive-correlation method and employed self-structured questionnaires. As to faculty profile, 38% were between 51-60 years old, majority were females (56.0%) were instructors who attained master’s level of education (42.0%). The respondents were rated adequate when measured as to the adequacy of the preparation of the syllabi in terms of course description, instructional delivery, major course activities, content development and course assessment. While the adequacy of syllabi utilization in terms of major course requirements, course content development and course assessment yielded to be adequate. The relationship between the faculty profile and the adequacy of syllabi preparation were not significant, while the relationship between the preparation and utilization of the syllabi by the faculty was significant except for the course content development and delivery. Generally, the difference on the adequacy of syllabi preparation and syllabi utilization were found to be significant. There were instructional problems of the faculty in the utilization of aids and devices and methods and strategies in teaching that needed administrative interventions.